Analisis Prinsip Good Governance dalam Penyelesaian Laporan Maladministrasi di Ombudsman Republik Indonesia Perwakilan Provinsi Jawa Tengah - Zhafif Henvianto, Muhammad; Widowati, Nina (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
This study analyzes the application of good governance principles in resolving maladministration reports at the Ombudsman of the Republic of Indonesia, Central Java Province Representative. Maladministration in public services negatively impacts society, necessitating effective oversight mechanisms to promote accountability and transparency. This research employs a descriptive qualitative method, analyzing primary data from interviews and secondary data from official documents. The study aims to describe and analyze the good governance principles and the obstacles to their implementation in addressing maladministration reports at the Central Java Ombudsman. The research adopts Mardiasmo's good governance theory, which encompasses accountability, transparency, democracy, and the rule of law. The Ombudsman plays a crucial role in supervising public services, however, challenges remain in the application of good governance principles, such as suboptimal accountability and transparency. The findings reveal that although good governance principles have been implemented, factors such as limited human resources affect the effectiveness of their execution. Strategic recommendations include integrating information technology, enhancing human resource training, and promoting public awareness of the Ombudsman’s role to optimize the application of good governance principles in resolving maladministration reports at the Ombudsman of the Republic of Indonesia, Central Java Province Representative. The study's results are expected to serve as a reference for improving public service governance, particularly in optimizing good governance principles and enhancing the efficiency of maladministration report resolution.